An algorithm for CAD tolerancing integration: Generation of assembly configurations according to dimensional and geometrical tolerances. (May 2015) - Louhichi, Borhen; Tlija, Mehdi; Benamara, Abdelmajid; Tahan, Antoine
Abstract: For several years, Digital Mock-Up (DMU) has been improved by the integration of many tools as Finite Element (FE) Analysis, Computer Aided Manufacturing (CAM), and Computer Aided Tolerancing (CAT) in the Computer Aided Design (CAD) model. In the geometrical model, the tolerances, which specify the requirements for the proper functioning of mechanical systems, are formally represented. The nominal modeling of the parts and assemblies does not allow the prediction of the tolerance impacts on the simulation results as the optimization of mechanical system assemblability. So, improving the CAD model to be closer to the realistic model is a necessity to verify and validate the mechanical system assemblability. This paper proposes a new approach to integrate the tolerances in CAD model by the determination of the configurations with defects of a CAD part, used in a mechanical system. The realistic parts are computed according to the dimensional and geometrical tolerances. This approach provides an assembly result closer to the real assembly of the mechanical system. The Replacement of the nominal parts by the realistic ones requires the redefinition of the initially defined assembly mating constraints. The update of the mating constraints is performed by respecting an Objective Function of the Assembly (OFA). Integrating tolerances in CAD allows the visualization and simulation of the mechanical assemblies' behavior in their real configuration and the detection of possible interference and collision effects between parts which are undetectable in the nominal state. Highlights: Tolerance integration in CAD model. The realistic modeling of the parts and assemblies. Prediction of the tolerance impacts. Updating the mating constraints.